2014
DOI: 10.1080/15578771.2014.965396
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Vertically Integrated BIM Curriculum in an Undergraduate Construction Management Program

Abstract: The popularity of Building Information Modeling (BIM) as an integral concept in the Architecture, Engineering, and Construction (AEC) industries has motivated its necessary inclusion in Construction Management (CM) education. Implementing BIM as a mainstream, elective or integrated subject within an established undergraduate curriculum is challenging due to limitations such as available teaching time, knowledge retention in students and the flexibility of the curriculum to adapt with a fast developing technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 5 publications
2
52
0
2
Order By: Relevance
“…Lack of available faculty to teach BIM 5,16,35 . Due to the high demand of BIM experts in the AEC industry, CM programs may not be able to hire competent new faculty who have been specifically and extensively trained with BIM in their education or industry experience.…”
Section: Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…Lack of available faculty to teach BIM 5,16,35 . Due to the high demand of BIM experts in the AEC industry, CM programs may not be able to hire competent new faculty who have been specifically and extensively trained with BIM in their education or industry experience.…”
Section: Challengesmentioning
confidence: 99%
“…The results indicated that 70% of the respondents had BIM covered in their curriculum. Most of them were teaching BIM for 3D coordination (82%), about half for scheduling (4D) (46%), and a third for estimating (5D) (35%) 16,33 .…”
Section: Current Conditionsmentioning
confidence: 99%
See 3 more Smart Citations